Can uterine rupture be prevented: Case series in Zainoel Abidin Hospital, Banda Aceh, Indonesia - Eva Febia; Mohammad Andalas (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2011)
The incidence of uterine rupture was devastating to the outcome of mother and the baby. This serial cases were to evaluate and analyze many factors which contributed to uterine rupture in Zainoel Abidin Hospital, Banda Aceh. Six serial cases of uterine rupture in almost one year (January 2011-Agustus 2011) were analyzed. There were six cases of uterine rupture. All cases happened in patients with previous caesarean sections. There were two cases in patients with classical previous caesarean section incision. One case happened in patient with previous caesarean section eleven months ago or short delivery interval. Two cases happened in prolonged of the second phase of labor more than 4 hours. One cases happened in second phase of labor less than one hour. Among six cases, there was one perinatal death in uterine rupture due to prolonged second phase of labor more than 5 hours. Previous classical uterine incision, second phase of labor, and inter-delivery time in previous Caesarean Section were contributing factors to the incidence of uterine rupture that can be predicted. So many ways can be used to prevent them